Memorial de Redonda : reinvenção e luta na produção da saúde dos povos do mar - Bezerra, Cleilton da Paz (2013)
The intercultural nature of the expansive processes of globalization is reflected in many aspects of the collective life of the peoples of the sea. In the community of Redonda, Icapuí (Ceará, Northeastern Brazil), these processes have over the past decades raised the level of conflict over land rights, subsistence fishing, education and health and placed the aboriginal environmental outlook at odds with the dictates of tourism. The purpose of this study was to understand the transformations in collective life as perceived by the peoples of the sea in Redonda with regard to the interface between culture, education, health and environment. The research was ethnographic, with in-depth descriptions based on Geertz. Autobiographies were produced from the narratives of the local residents, including fishermen, shellfish gatherers, farmers, seniors, youths and children. The early settlement of Redonda produced a community consisting of closely related families living off subsistence agriculture, fishing and barter. The unique land/sea interaction of Redonda led to the emergence of a treasury of symbolism and rituals of care and cure in harmony with nature. Originally, life in the community emphasized the collective dimension, the use of common space and solidary practices of care. Underpinned by the principles of the basic ecclesial communities, the local sites of memory have become symbols of resistance where belief and religiosity provide a setting for utopian thought and, under extreme circumstances, a movement towards the novel-but-feasible. Tensions involving lobster fishing have transformed the sea into a battle field of competition, war and death. A degrading form of tourism attempts to submit to capitalist interests the relation between society and nature while multifaceted vulnerabilities are deepened as drug addiction encroaches insidiously on the community, creating a scenario of silent war reinforced by the conflicts at sea. However, local popular movements are producing a body of health knowledge and entertaining the prospect of reinventing resistance through art. The drama troupe “Flor do Sol” has found in stage poetry a form of empowerment and reaffirmation of the ethnic and cultural uniqueness of Redonda. In gatherings by the seashore, popular education, such as the production of knowledge through art, deconstructs prefabricated world views tied up with gender inequalities and environmental injustice. On stage, social critique and utopia are expressed in the form of health promotion for the peoples of the sea. Institutionally, in the present context, hope acquires the characteristics of the public health care networks and infiltrates the living territories in search for the multidimensionality which distinguishes the health production of the peoples of the sea. In the web of meaning with which culture is woven, the production of health is reaffirmed as production of life. The study reveals the transformations which occur in the dialectic between adjustment and resistance and which reverberate in the conditions of life of the peoples of the sea.